Hydrogeochemical Features and Genesis of Confined Groundwater and Health Perspectives for Sustainable Development in Urban Hengshui, North China Plain - Yong Xiao; Kui Liu; Qichen Hao; Jianfeng Li; Yunhui Zhang; Weizhe Cui; Limao qin; Qiuming Pei (Journal of Chemistry)
Groundwater in confined aquifers is the preferred water resource worldwide, and its hydrochemical quality is the premise for sustainable development. A systematic hydrogeochemical research was conducted to get insight into the hydrochemical characteristics, genesis, and potential health threats of confined groundwater, based on analytical data of 45 groundwater samples collected from the urban area of Hengshui, Central North China Plain (NCP). The results showed most groundwater had desirable hydrochemical quality with a nearly neutral to slightly alkaline nature and dominantly soft-fresh Cl-Na face. Solute chemistry was governed by rock-water interaction including minerals dissolution and ion exchange, but out of the anthropogenic influences. All nitrogen pollutants and Zn were within the desirable limit, while F−, Mn, and Fe were beyond the desirable limit recommended by WHO in 28.9%, 15.6%, and 68.9% of samples. Overall chronic health risk from these toxic elements was identified in terms of various populations and mainly contributed by F−. Infants were more prone to the health risks of aqueous pollutants. Differential water supplies based on hydrochemical quality are recommended, and water improvement measures are suggested to be conducted aiming at the harmful fluoride in confined groundwater. The present research could provide valuable references for the health sustainability of confined groundwater utilization in sedimentary plains like NCP worldwide.